Logarithm question equation I'm stuck on an equation : ( log 8 </msub> &#

Willow Pratt 2022-06-30 Answered
Logarithm question equation
I'm stuck on an equation :
( log 8 x ) 2 + 2 log 8 x + 1 = 0
I've played with it without any success. Any indications would be greatly appreciated...
Thank you!
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

conveneau71
Answered 2022-07-01 Author has 17 answers
You've got u 2 + 2 u + 1 = 0, where u = log 8 x
Factoring, you get ( u + 1 ) 2 = 0, which entails that u = 1
If log 8 x = 1 then 8 1 = x, i.e. x = 1 8
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2021-10-24

how do you use the one-to-one property of property of logarithms to solve? step by step please
log(x+3)log(x)=log(74)

asked 2022-03-25
Denesting Logarithmic expressions
log7(log2(3))+log7(log5(6))+log7(log11(12))=log7(1)+log7(log5(3))+log7(log11(6))
This can only be simplified by using the sum to product rule and noticing that of the n! possible permutations that 12 is a power of 2. Because N is small and the relationship between 2 to 12 is simple this can be solved trivially. How does one go about simplifying much more complex logarithmic identities in polynomial time?
asked 2022-06-21
Logarithmic functions?
I am stuck on this question which as follows:
log ( x ) + log ( x 3 ) = log ( 10 x )
I have tried the following and not sure if I am doing it correctly...
1)
log ( x ) + log ( x 3 ) = log ( 10 x ) log ( ( x ) ( x 3 ) ) = log ( 10 x )
log ( x 2 3 x ) = log ( 10 x ) x 2 3 x = 10 x
x 2 13 x = 0 x = 0 , x = 13
2)
log ( x ) + log ( x 3 ) = log ( 10 x )
log ( x ) + log ( x ) log ( 3 ) = log ( 10 x )
x + x 3 = 10 x x = 3 / 8
Are these approaches on the right path?
asked 2022-08-20
Am I allowed to apply L'Hospital's Rule inside of the natural logarithm function?
I have the following limit:
lim x ln ( 2 x 2 + 1 x 2 + 1 )
If I was finding the limit of only the terms inside the natural log function, I would have the indeterminate form:

I want to know if I am allowed to apply L'Hospital's Rule to only the inside terms while ignoring the natural logarithm function, giving me the answer:
ln ( 4 x 2 x ) = ln ( 2 )
asked 2022-10-21
How to clear variable v from logarithmic equation
I have the following:
6.4 = log 5 v 0.1 50 + v
I would like to know how to solve the equation in order to get v's value. Thank you very much.
asked 2022-06-30
Dividing factorials
I'm told that ( n + 1 ) ! ( n + 2 ) ! simplifies to 1 n + 2 , but I dont understand how this works.
Could someone explain the theory of how to divide factorials like this?
asked 2021-11-06
Use the properties of logarithms to expand the quantity.
lnx2(y3z4)